1999
DOI: 10.1183/09031936.99.13613919
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide and sputum eosinophil markers of inflammation in asthmatic children

Abstract: The relationship between nitric oxide in exhaled air, levels of sputum eosinophils, sputum eosinophil cationic protein (ECP) and urinary eosinophil protein X (EPX) excretion has not yet been investigated in corticosteroid-dependent childhood asthma.Therefore, taking 25 children with stable asthma (mean age 11.2 yrs) treated with inhaled corticosteroids and nine nonatopic healthy control children (mean age 12.8 yrs) the level of exhaled NO was measured by means of a chemiluminescence analyser before and after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(42 citation statements)
references
References 32 publications
2
36
0
4
Order By: Relevance
“…urinary EPX excretion, and eosinophilic airway inflammation in asthmatics (12,24). Hence the circadian variation of FeNo and urinary EPX found in this study may indicate a substantial nocturnal increase in activation of eosinophils as previously investigated in blood samples by Wempe et al (25).…”
supporting
confidence: 51%
“…urinary EPX excretion, and eosinophilic airway inflammation in asthmatics (12,24). Hence the circadian variation of FeNo and urinary EPX found in this study may indicate a substantial nocturnal increase in activation of eosinophils as previously investigated in blood samples by Wempe et al (25).…”
supporting
confidence: 51%
“…The most extensively studied biomarker is FeNO, which has been reported to reflect both airway and tissue eosinophilia [142][143][144]. FeNO can be measured in a noninvasive standardised way and is an attractive technique for use in children, usually from school age onwards [144][145][146].…”
Section: Fenomentioning
confidence: 99%
“…Measurement of F eno as an indicator of pulmonary infl ammation is relatively simple and inexpensive compared with other biomarkers, so there is great interest in the potential role for using F eno data in asthma management. F eno level has been shown to correlate with lung function, sputum eosinophil levels, and methacholine responsiveness, [9][10][11][12][13][14][15][16][17] and, therefore, may provide a noninvasive change of Ն 10 ppb for those with lower categories of infl ammation. We applied this algorithm, modifi ed for pediatric cut points (if F eno level increased by Ն 7 ppb for those with F eno values , 35 ppb or Ն 20% for those with F eno Ն 35 ppb) and found that a "significant" change in F eno level from the previous visit did not predict future health-care use ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…These are less likely given prior studies that demonstrate reproducibility of F eno measurements 34,35 and the strong, existing evidence of correlation between eosinophilic airway infl ammation and F eno level. 9,11,[13][14][15][16][17] There were limitations to the study design that warrant consideration. As our study population was limited to children in Baltimore City, results may not be generalizable to other populations.…”
Section: Role Of Sponsorsmentioning
confidence: 99%